Synthesis and characterization of poly (3,4-ethylene-dioxythiophene) nanomaterials - Liu, Ling Xian. (2010)
The chemical reaction method is applied to produce poly (3,4-ethylene-dioxythiophene). In the polymerization step, reactant molar ratio, reaction temperature and reaction time have been investigated. The dried solid PEDOT was characterized by the equipments: Fourier Transform Infrared Spectroscope (FTIR), Thermogravimetric Analysis (TGA), and Differential Scanning Claorimetry (DSC). The variation of those reaction parameters had no significant effect on the properties of PEDOT in the bulk state. In the nanostructure growth step, it has been proved that nanostructure of the polymer formed is mainly determined by organic solvents at different concentrations. The equipments used for characterization included Scanning Electron Microscope (SEM), Ultraviolet-Visible Spectroscope (UV-Vis). Major solvents were used are methanol, acetonitrile, bromobenzene and ortho-dichlorobenzene. The nanostructures obtained varied from nanorods, nanofibres, nanowires to microrods depending on the different solvent applied.